Digitisation Perspectives - Rikowski, Ruth.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
This book examines various views and perspectives on digitisation. Topics covered include electronic theses, search engine technology, digitisation in Africa, citation indexing, reference services, the Scholarly Publishing and Academic Resources Coalition, new media and scholarly publishing. The final chapter explores virtual libraries, and poses some interesting questions for possible futures. The book will be of particular interest to information professionals, educators, librarians, academics and I.T. and knowledge experts.
Keywords: Education; Education -- Philosophy; Education; Educational Philosophy